The phosphoinositide code is read by a plethora of protein domains. (3rd July 2021) - Overduin, Michael; Kervin, Troy A.
ABSTRACT: Introduction: The proteins that decipher nucleic acid- and protein-based information are well known, however, those that read membrane-encoded information remain understudied. Here, we report 70 different human, microbial and viral protein folds that recognize phosphoinositides (PIs), comprising the readers of a vast membrane code. Areas covered: Membrane recognition is best understood for FYVE, PH and PX domains, which exemplify hundreds of PI code readers. Comparable lipid interaction mechanisms may be mediated by kinases, adjacent C1 and C2 domains, trafficking arrestins, GAT and VHS modules, membrane-perturbing annexins, BAR, CHMP, ENTH, HEAT, syntaxin and Tubby helical bundles, multipurpose FERM, EH, MATH, PHD, PDZ, PROPPIN, PTB and SH2 domains, as well as systems that regulate receptors, GTPases and actin filaments, transfer lipids, and assemble bacterial and viral particles. Expert opinion: The elucidation of how membranes are recognized has extended the genetic code to the PI code. Novel discoveries include PIP-stop and MET-stop residues to which phosphates and metabolites are attached to block phosphatidylinositol phosphate (PIP) recognition, memteins as functional membrane protein apparatuses and lipidons as lipid 'codons' recognized by membrane readers. At least 5% of the human proteome senses such membrane signals and allows eukaryotic organelles and pathogens to operate and replicate.